Deeply-scaled GaN-on-Si high electron mobility transistors with record cut-off frequency fT of 310 GHz. (22nd November 2019) - Xie, Hanlin; Liu, Zhihong; Gao, Yu; Ranjan, Kumud; Lee, Kenneth E.; Ng, Geok Ing
Abstract: A deeply-scaled GaN-on-Si high electron mobility transistor with a record-high cut-off frequency ( f T ) of 310 GHz has been demonstrated. The device has an InAlN/GaN heterojunction structure, a source–drain spacing of 400 nm, and a gate length of 40 nm. The device exhibited a high drain current of 2.34 A mm −1, a peak transconductance of 523 mS mm −1, and a gate-to-drain breakdown voltage ( BV gd ) of 15 V. A Johnson's figure-of-merit (FOM =  f T  ×  BV ) of 4.65 THz V has been achieved, which is comparable to those reported in GaN-on-SiC. These results indicate GaN-on-Si transistors are promising in low-cost emerging mm-wave applications.